L’enceinte médiévale de Blois : quelques précisions sur un ensemble méconnu - Marie Lafont (Revue Archéologique du Centre de la France)
The medieval city wall of Blois was studied on a master II thesis framework, directed by Alain Salamagne. The issue was to identify and study all documentary sources of the city wall. The study of the architecture remains, in combinaison with the iconographic and written sources allowed to make on interpretation of the construction datation (during the three firt quarters of the xiiith century), and to identify all the modification’s phases of the city wall. In this way, after the several reinforcements during the xivth century, the fortification was partially adapt to fire weapans during the first half of the xvth century. The city wall was abandoned at the end of the xvith century then progressively destroyed during the late medieval period.